Lighting circuit diagnostic tools - Muhammad Azam, Mohd Nasir (2021)
Power failure is a common issue that arises when electrical faults occur, leading to discontinuity of electrical supply to industrial construction. Power continuity is very important for industrial customers since some of their appliances or machinery, such as pumps or machines, require a continuous electrical supply for every system. The fault in the system, however, would cause the earth leakage circuit breaker (ELCB) and interrupt the supply of all appliances and disturb the system as well. Due to short circuit, ground fault or overloading, failure may occur. Fault position identification is therefore important to ensure continuity of power and reliability in which, once detected, the fault can be isolated from the device. An automated fault detection system which is necessary to develop in order to face the problem.